THE IMPACT OF TEACHER-STUDENT INTERACTION ON LEARNING MOTIVATION AND CLASSROOM ENGAGEMENT - Zhang, W (International Journal of Literature and Language Studies, 2026)
Teacher-student interaction plays a central role in creating a positive educational environment and increasing learning motivation. The aim of this study was to analyze the influence of supportive teacher-student relationships on classroom engagement. The results show that respectful communication, emotional support, constructive feedback and teacher encouragement increase student participation, confidence and academic persistence.